Changing conservation strategies in Europe: a framework integrating ecosystem services and dynamics - Haslett, J; Berry, P; Bela, G; Jongman, R; Pataki, G; Samways, M; Zobel, M (Springer, 2010)
Protecting species and their habitats through the designation and management of protected areas is central to present biodiversity conservation efforts in Europe. Recent awareness of the importance of ecosystem dynamics in changing environments and of human needs for the sustainable provision of ecosystem service expose potential weaknesses in current European conservation management strategies and policy. Here we examine these issues in the light of information gained from reviews, workshops, interviews and discussions undertaken within the RUBICODE project. We present a new conceptual framework that joins conventional biodiversity conservation with new requirements. The framework links cultural and aesthetic values applied in a static environment to the demands of dynamic ecosystems and societal needs within social-ecological systems in a changing Europe. We employ this framework to propose innovative ways in which ecosystem service provision may be used to add value to traditional conservation approaches by supporting and complementing present European biodiversity conservation strategy and policy while remaining within the guidelines of the Convention on Biological Diversity.